An empirical analysis of stock and bond market liquidity - Tarun Chordia; Asani Sarkar; Avanidhar Subrahmanyam (Federal Reserve Bank of New York, 2003)
This paper explores liquidity movements in stock and Treasury bond markets over a period of more than 1800 trading days. Cross-market dynamics in liquidity are documented by estimating a vector autoregressive model for liquidity (that is, bid-ask spreads and depth), returns, volatility, and order flow in the stock and bond markets. We find that a shock to quoted spreads in one market affects the spreads in both markets, and that return volatility is an important driver of liquidity. Innovations to stock and bond market liquidity and volatility prove to be significantly correlated, suggesting that common factors drive liquidity and volatility in both markets. Monetary expansion increases equity market liquidity during periods of financial crises, and unexpected increases (decreases) in the federal funds rate lead to decreases (increases) in liquidity and increases (decreases) in stock and bond volatility. Finally, we find that flows to the stock and government bond sectors play an important role in forecasting stock and bond liquidity. The results establish a link between 'macro' liquidity, or money flows, and 'micro' or transactions liquidity.
Keywords: G10; G14; G23; E52; 330; Aktienmarkt; Rentenmarkt; Gesamtwirtschaftliche Liquidität; VAR-Modell; Volatilität; Geldpolitik; USA